Peran Teknologi Pendidikan dalam Perspektif Merdeka Belajar pada Abad 21 di Sekolah Dasar - tri yudha setiawan (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
This study aims to describe the role of educational technology in the perspective of independent learning in the 21st century in primary schools in the teaching and learning process. This research is a qualitative research. The type of research used is library research. Sources of data in the study were obtained from research journals that have been published and indexed by sinta and google scholars. The publication article is taken from the last 7 years issue. In this study, there were 7 articles as data sources. The data analysis technique used is content analysis technique. The results of the study show that in the 21st century the role of educational technology is very large in learning. This can be seen in the implementation of independent learning which gives freedom to schools, teachers, and students in the teaching and learning process at the elementary school level unit. The role of educational technology is to improve the quality of education by facilitating the teaching and learning process, and tools to facilitate teaching and learning in the classroom.